Performance evaluation of massive data standardization using multicore CPU and GPU - Ahmed Dheyab, Saad; Buthainah Fahran Abed, Dr.; Mohammed Najm Abdullah, Dr. (International Journal of Engineering and Technology, 2018)
Standardization is one of the most important methods for the preprocessing phase in machine learning. It increases the quality of the results in terms of accuracy. Researchers have focused on the development of these preprocessing methods to suit the diversity of data generated from different sources. In this paper, three types of standardization methods (z score, min-max, log2) were applied to a mas-sive dataset using three different preprocessing approaches (CPU single core, CPU multicore open MP, and GPU) and evaluated their performance. From the results, these approaches showed a faster GPU performance compared to the conventional CPU performance. Â